Leadership and change management: a case study of Pemancar - Abdullah, Zarifah; Abdul Khalid, Siti Nabiha (World Scientific Publishing, 2012)
This case examines the implementation of a new organizational culture in a newly taken-over Malaysian subsidiary by a European-based multinational company.The new organizational culture is geared towards high performance, increased accountability, value creation, and high quality and better communication.However, organizational members who were very much accustomed to their prevailing organizational culture found it difficult to understand the need for them to change as they had done well in the past.The features of the new culture, the structural changes that have taken place and how the organizational members felt about the change process and their reactions towards the change are explicated in the case.The case also highlights the various issues and challenges that took place and which needed to be tackled in the management's effort to ensure the successful integration and internalization process of the change in organizational culture.